Handbook of toxicology - edited by Michael J. Derelanko; PhD; DABT; FATS; Carol S. Auletta; DABT; RAC; MBA. (CRC Press, Taylor & Francis Group, 2014)
The Handbook of Toxicology, Third Edition provides an updated practical reference source for practicing toxicologists in the pharmaceutical and chemical industries, contract laboratories, regulatory agencies, and academia. Written by experts in their specific toxicology fields, the chapters provide both fundamental and applied information. Topics range from General Toxicology, to Genetic Toxicology, Human Clinical Toxicology, Histopathology, Clinical Pathology, Metabolism and Toxicokinetics, Risk Assessment, and more